PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN TENDER PROYEK DI DINAS PEKERJAAN UMUM SOLOK SELATAN BERBASIS WEB - Lusi Tridarni; Elfi Tasrif; Yeka Hendriyani (Universitas Negeri Padang, 2015)
The problem in this final project is bidding tender project at the Department of Public Work of South solok works manually. The manually process like registering company and all participants who have registered will be collected in a room so it would make any difficult for participants who are outside the area. The development of information technology has a lot of influence in various fields. One of the information technology is growing rapidly is a web-based information systems. The utilization of this web-based information technology within an organization can be implemented on the Victory Decision Support System Project Tender, the incoming data will be stored in a database and the database as data processing. Tender decision support system project is using Analytical Hierarchy Proces method is to determine the criteria that will be used to calculate the weights. The criteria used in this system is the administrative, technical and price. Each criterion is calculated and the result will be used to determine the winning bidder. Keyword : Analityc Hierarchy Process, Database, Decision Support System,Tender, Web